FUNDAMENTOS CULTURALES, SOCIALES Y ECONÓMICOS DE LA AGROECOLOGÍA - Martínez Castillo, Róger (2023)
Agroecology as an ecological approach to the agricultural process, not only covers food production, but also, takes into account social, economical and cultural aspects related and influencing production. There are two totally different ways of appropriating the agroecosystem: one, the traditional agrarian manner (rural, indigenous), the other- the agroindustrial manner. They conform two ways to understand, manage and utilize agroecosystems.